Analisis Manajemen Rantai Pasok Beras dengan Pendekatan Scor Model (Studi Kasus Pada CV. Santi Jaya Barokah Kabupaten Kuningan) - Faridz Adi Nurmansyah; Robi Awaluddin; Ayus Ahmad Yusuf (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2022)
Supply Chain Management is a method, tool, or one that starts from supplying raw materials, producing goods to making deliveries to final consumers. CV Santi Jaya Barokah which is engaged in Agribusiness, CV Santi Jaya Barokah experienced various obstacles such as delays in delivery, the search for raw materials that meet company standards and CV Santi Jaya Barokah does not yet have a performance measurement to evaluate the company's performance. Therefore, this study was made to find out the most vital problems in the company by creating a supply chain performance measurement system, this performance measurement system was carried out using the Supply Chain Operation Reference (SCOR) model with the assistance of the Expert Chice application. From the identification results, there are 14 Key Performance Indicators (KPIs) that represent the company. From the analysis results obtained aggregate achievement of 97%. Overall the company's performance is going well, the company only needs to improve its performance in the upstream part, namely those related to suppliers and processing systems that still do not meet the company's targets.